144 In Vivo Synergistic Effect of Checkpoint Blockade and Radiation Therapy Against Chordomas in a Humanized Mouse Model. Issue Volume 65:Issue CN(2018)Supplement 1 (16th August 2018) - Ishida, Wataru; Wang, Hui; McCormick, Kyle; Mahajan, Aayushi; Feldstein, Eric; Lim, Michael; Canoll, Peter D; Bruce, Jeffrey N; Yang, Yong-Guang; Lo, Sheng-fu L
Abstract: INTRODUCTION: Currently, there are no murine chordoma cell lines nor transgenic mouse models of chordomas, which prevents us from investigating the interaction between murine chordomas and murine immune cells. Thus, to scrutinize immunotherapy (IT) against chordomas, the development of a humanized mouse model of chordomas, where human thymus and CD34 +  stem cells as well as human chordomas are co-transplanted to engraft human immune system into mice, is imperative. We aimed to develop this model and investigate synergistic effect between IT and radiation therapy (RT) against chordomas using this model. METHODS: Fifteen 10- to 12-wk-old NSG mice were sublethally irradiated and then implanted with human fetal thymic tissue and CD34 +  stem cells, whose HLA type is partially matched with that of the U-CH1 chordoma cell line. Reconstitution of immune cells in NSG mice was confirmed 8 wk post-transplantation and then each animal was injected with U-CH1 subcutaneously. Next, they were treated for 4 wk as follows: (A) control (n = 3), (B) anti-human-PD-1 antibodies (n = 4), (C) RT + isotype antibodies (n = 3, 8 Gy × 4), (D) anti-human-PD-1 antibodies and RT (n = 5). Anti-tumor activities were monitored via tumor size, flow cytometry, qRT-PCR, and immunohistochemistry. RESULTS: One week after the treatment, on the irradiated side, (D) demonstrated lowest tumor volume, highest number of human PBMCs, highest % of CD8 +  human T cells, highest % of CD45RO+CD4 +  human T cells, and lowest % of PD-1+CD8 +  human T cells in the tumors via flow cytometry, and highest IFN-gamma in the tumors via qRT-PCR, compared to the other groups with statistical significance. CONCLUSION: We demonstrated that this humanized mouse model could be a revolutionary platform to investigate IT against rare cancers such as chordomas, where murine equivalents are unavailable. The direct synergistic effect between IT and RT against chordoma was observed, evidenced by lowest tumor volume, highest cytotoxic T cells, and memory T cells.